A Descriptive Study On Teaching Vocabulary For The Fourth Grade Students Of SD N 03 Bejen, Karanganyar In 2011/2012 Academic Year - Permatasari, Ramadhani Ratna; , Dr. Anam Sutopo, S. Pd. M. Hum; , Nur Hidayat, M. Pd (2015)
This research aims at describing the process of teaching-learning vocabulary for the fourth grade students of SD N 03 Bejen, Karanganyar. It is conducted to describe the process, goal, material, the method of teaching vocabulary, problems faced by teacher and problems solving applied by the teacher at SD N 03 Bejen, Karanganyar. The objectives of the study are to explain the process of teachinglearning vocabulary at fourth grade students, to identify the problems faced by teacher in teaching vocabulary and to classify the strategies implemented by teacher to solve the problems. This research paper belongs to descriptive qualitative research. Data of the research are taken from event, informant, and document. The techniques of collecting data are the interview, observation, and documentations. The result of analysis shows that the goals of teaching vocabulary are to improve and develop students' vocabulary. The method applied by the teacher is Grammar Translation Method and Direct Method. The teacher faces several problems in teaching vocabulary such as class management, students' different ability in acquiring vocabulary, and different motivation of the students. The problem solving applied by the teacher are by using group work to manage the number of students that overload and giving advices and motivation about the importance of activity in vocabulary class.